NTERACTION WITH THE FAMILY AS A CONDITION FOR THE FORMATION OF THE NATIONAL AND LANGUAGE PERSONALITY OF THE PRESCHOOL CHILD - Ковшар, Олена; Куц, Катерина (SWorldJournal, 2024)
The article is devoted to the problem of the formation of the national speech personality of a preschool child. The relevance of the chosen topic is determined by the task of modern society to develop a preschool child as a future citizen, patriot in the